STUDI LITERATUR IMPLEMENTASI PEMBELAJARAN PJOK BERBASIS DARING UNTUK MENINGKATKAN MOTIVASI BELAJAR PJOK - Muhammad A.Permana, - (2022)
This research aims to know the implementation of online-based physical education learning to increase student motivation in learning sport physical education and health. The benefits of this research is to increase knowledge and experience for researchers in applying knowledge in dealing with real problems, and also as a guide for increasing online-based student learning motivation and making maximum use of learning resources so they can get higher learning outcomes. The method used in this research is SLR (systematic Literatur Review) method. The articles used in this study were 11 articles with the article screening process using the PRISMA (Preferred Reporting Item For Systematic Reviews and Meta Analysis) diagram. There's a conclusion of the application of sport physical education and health online learning that the teacher must be able to pack varied learning to increase motivation to learn physical education study. In the application of online learning, you can use applications such as zoom, google meet, google classroom, WA groups, etc. Keywords: motivation, pjok, e-learning